HUBUNGAN KETERSEDIAAN FASILITAS PENUNJANG TERHADAP KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU YANG BEKERJA SEBAGAI TENAGA KESEHATAN - B Budiyanto; Arnika Dwi Asti; Podo Yuwono (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
In 2013, UNICEF states that 136.7 million babies were born around the world and only 32.6% were exclusively breastfed. Riskesdas data coverage in the Indonesian Exclusive breastfeeding fluctuate and tend to decrease from 31.0% in 2010 to 30.2% in 2013 28% exclusive breastfeeding failure because mothers have to work. A research conducted in the health center Hartatik Bahorok Langkat (2010) obtained 20% of health workers providing exclusive breastfeeding and 80% did not give exclusive breastfeeding. From the results of research in the village Yuliarsi Sawangan Depok West Java (2012), 66.7% of working mothers had supporting facilities for exclusive breastfeeding in the workplace and 33.3% did not have supporting facilities. In PKU Muhammadiyah Gombong Hospital there are 32 female health workers who have toddlers.This study is to determine the correlation between the availability of supporting facilities for exclusive breastfeeding women with the succeed of exclusive breastfeeding of mothers who work as health care givers in PKU Muhammadiyah Gombong Hospital. This study  is an analytic survey research using cross sectional approach. The samples consist of 32 respondents with 6 months - 5 years children taken by using total sampling technique. Data processing technique is SPSS 17 computer program with chi-square statistical test. Of 3.1% of respondents give exclusive breastfeeding and 96.9% are nonexclusive. 90.6% of respondents give formula milk. Based on SPSS calculations using chi-square test no facilities are associated with exclusive breastfeeding. Keywords; Exclusive breastfeeding, facilities